1999
DOI: 10.1117/12.335772
|View full text |Cite
|
Sign up to set email alerts
|

<title>Hyperspectral analysis of fecal contamination: a case study of poultry</title>

Abstract: Optical detection of fecal contamination on poultry carcasses is addressed in this paper.Specifically, a hyperspectral imaging system with a spectral range in the visible and near-infrared is used to capture imagery of a poultry carcass. A number of image processing routines are investigated for their effectiveness and efficiency at detecting feces. Based on the need for speed, the more simplistic mathematical operations seem to hold the most promise for detecting contaminated carcasses in real-time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Hyperspectral imaging technologies are also being utilized in medical (Harvey, Lawlor, McNaught, & Fletcher-Holmes, 2002;Levenson, Wachman, Niu, & Farkas, 1998) biological, agricultural, and industrial areas (Heitschmidt, Lanoue, Mao, & May, 1998;Lu & Chen, 1998;Lu, Chen, Park, & Choi, 1999;Willoughby, Folkman, & Figueroa, 1996). Furthermore, this great potential hyperspectral imaging technology has been applied for food quality and safety (Hahn, 2002;Lu & Chen, 1998;Lu et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…Hyperspectral imaging technologies are also being utilized in medical (Harvey, Lawlor, McNaught, & Fletcher-Holmes, 2002;Levenson, Wachman, Niu, & Farkas, 1998) biological, agricultural, and industrial areas (Heitschmidt, Lanoue, Mao, & May, 1998;Lu & Chen, 1998;Lu, Chen, Park, & Choi, 1999;Willoughby, Folkman, & Figueroa, 1996). Furthermore, this great potential hyperspectral imaging technology has been applied for food quality and safety (Hahn, 2002;Lu & Chen, 1998;Lu et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…Kim et al (2001) established a laboratory−based hyperspectral imaging system combining the features of imaging and visible/near−infrared (Vis/NIR) spectroscopy to simultaneously acquire spectral and spatial information for various food commodities, and Kim et al (2002aKim et al ( , 2002b used hyperspectral imaging methods for fecal contamination detection on apples. Heitschmidt (1998) used hyperspectral analysis for fecal contamination of poultry products, and Chen et al (1998), Park et al (2002), and Windham et al (2001) showed methods of using hyperspectral imaging for detecting contamination of chicken carcasses. Lu and Chen (1998) and Lu et al (1999) found that only two or three essential spectral bands were required for on−line imaging applications to extract unwholesome conditions in food products.…”
mentioning
confidence: 99%
“…In the agricultural side, hyperspectral imaging technologies were applied for grass characterization, sugar contents in melon, apple bruise detection, wheat scab detection, and poultry fecal detection (Heitschmidt et al, 1998;Schut et al, 2002;Tsuta et al, 2002;Lu et al, 1999;Delwiche and Kim, 2000;Kim et al, 2001;Mehl et al, 2001;Windham et al, 2002Windham et al, , 2003bLawrence et al, 2002Lawrence et al, , 2003Park et al, 2003aPark et al, , 2003b.…”
mentioning
confidence: 99%